2017
DOI: 10.25205/2541-9447-2017-12-2-20-27
|View full text |Cite
|
Sign up to set email alerts
|

On Determination of the Mechanism of Mach Wave / Bow-Shock Interaction

Abstract: Работа выполнена при финансовой поддержке Российского фонда фундаментальных исследований (проект № 16-01-00743-а «Исследование механизмов воздействия слабых ударных волн на ламинарно-турбулентный переход и теплообмен в сверх-и гиперзвуковом пограничном слое»).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 2 publications
0
1
0
Order By: Relevance
“…Typical case is when a weak shock wave falls from the side wall to the leading edge of the models [4][5][6][7][8]. Experiments have shown that in these cases the transition in the boundary layer of models is not described itself in the framework of traditional concepts.…”
Section: Introductionmentioning
confidence: 99%
“…Typical case is when a weak shock wave falls from the side wall to the leading edge of the models [4][5][6][7][8]. Experiments have shown that in these cases the transition in the boundary layer of models is not described itself in the framework of traditional concepts.…”
Section: Introductionmentioning
confidence: 99%